A first principles investigation on the interaction of oxomolybdenum porphyrin with Q2 - Oxomolybdenum porphyrin as a catalyst for oxygen reduction - Kubota, Yoshiyuki (Animo Repository, 2006)
We investigated the interaction of oxomolybdenum porpyhrin (MoO(por)) with 0% by using first principles calculations. Our calculations indicate that the adsorbed O2 on MoO(por) does not take an end-on configuration, but a side-on configuration to become more stable. These results can be understood from the differences in the molecular orbital energies and the valence electron densities. The geometric parameters of MoO(por) and MoO(por) (O2) with a side-on configuration of O2 are in good, agreement with experimental results. © 2006 The Surface Science Society of Japan.